Beliefs and Attitudes of Ophthalmologists Regarding SLT as First Line Therapy for Glaucoma. Issue 10 (October 2020) - Bonafede, Lucas; Sanvicente, Carina T.; Hark, Lisa A.; Tran, Judie; Tran, Evelyn; Zhang, Qiang; Costello, Rose; Myers, Jonathan S.; Katz, L. Jay
Abstract : Precis: Targeted educational interventions for physicians may be useful in increasing adoption of selective laser trabeculoplasty (SLT) as first line therapy for the treatment of glaucoma. Purpose: SLT is a safe and effective first line treatment for glaucoma, however, it is underutilized. To evaluate barriers for the widespread adoption of this procedure, we assessed the beliefs and attitudes of ophthalmologists. We developed an educational intervention directed to physicians to increase the consideration of SLT earlier in the glaucoma treatment paradigm. Subjects and Methods: In this prospective study, an online survey and educational slide presentation was sent to a group of comprehensive ophthalmologists, ophthalmology residents, and glaucoma specialists. Subjects were asked to respond to questions regarding their beliefs and attitudes towards SLT before and after watching the educational slide presentation. Results: A total of 53 subjects were enrolled. Before watching the slide presentation, 85% of subjects stated they offer SLT to newly diagnosed patients, although only 28% preferred it over medications. While 52% of physicians reported between 0% and 10% of their newly diagnosed patients receive laser therapy, 47% said they would use it as a first line therapy for all or most newly diagnosed glaucoma patients. Most subjects (94%) stated the educational slide presentation convinced them that SLT is appropriate as a first line therapy for treatment of open angle glaucoma. Conclusions: A better understanding of the barriers for utilizing SLT as a first line therapy provides valuable information to help increase the adoption of this safe and effective procedure. A targeted educational intervention may improve acceptance of SLT as first line therapy for open angle glaucoma. Abstract : Supplemental Digital Content is available in the text.